ANALISIS LEBAR POTONGAN BOTOL PLASTIK IDEAL PADA PEMBUATAN FILAMEN PET MENGGUNAKAN MESIN 3D PULTRUSION HIKU TECH - Ranteliling, Christian Imanuel; Misrianto; Andivas, Marulan (Jurnal Ilmiah Teknik Industri, 2025)
Hiku Tech 3D Pultrusion Machine is a PET filament making machine from PET plastic bottle waste designed by Industrial Engineering students of University of Balikpapan. The machine still needs adjustment in handling the size of PET plastic bottle pieces with different widths. The width of the cut can affect the quality of PET filament and the time of making PET filament, if the cut is too wide or narrow. This study aims to determine the ideal cut width of plastic bottles in PET filament making by looking at the quality of PET filament results and the effect of plastic bottle cut width on PET filament making time. This research uses the method of checking the quality of filament results and the simple linear regression method. The scoring results of the 8mm cut width produced a score of 2 for 23 samples, the 9mm cut width produced a score of 4 for 18 samples, and the 10mm cut width produced a score of 2 for 20 samples. The results of linear regression analysis state that the width of 8mm and 10mm pieces has no positive and significant effect on the time of making PET filaments, while the width of 9mm pieces has a positive and significant effect on the time of making PET filaments. Thus, in the manufacture of PET filaments with cut widths of 8mm, 9mm, and 10mm plastic bottles, it was found that the ideal cut width in the manufacture of PET filaments is a cut width of 9mm.